A wear-resistant enhanced flux-cored welding wire and its preparation method and application

The enhanced flux-cored welding wire, with a specific composition and laser cladding process, addresses the limitations of traditional wires by forming stable hard phases and improving wear resistance, meeting high-end manufacturing needs.

CN116652442BActive Publication Date: 2025-01-03ZHENGZHOU RES INST OF MECHANICAL ENG CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310163458.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-24
Publication Date
2025-01-03
Estimated Expiration
2043-02-24

AI Technical Summary

Technical Problem

Traditional iron-based flux-cored welding wires have low coating hardness and wear resistance, limiting their application in high-end, precision, and automated manufacturing, while using diamond particles in laser cladding leads to carbonization and cracking due to high energy density, reducing their effectiveness.

Method used

A wear-resistant enhanced flux-cored welding wire composed of specific raw materials, including diamond micropowder, tungsten powder, and other alloys, wrapped in an outer skin, which is used in laser cladding with argon protection to form a metallurgically bonded coating on substrates like Q235 steel.

Benefits of technology

The enhanced flux-cored welding wire significantly improves the hardness and wear resistance of the cladding coating, forming stable hard phases and enhancing bonding strength, thus extending the service life of mechanical parts.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention belongs to the technical field of welding materials, and specifically relates to a wear-resistant enhanced flux-cored welding wire and its preparation method and application. The wear-resistant enhanced flux-cored welding wire of the present invention comprises an outer skin and a flux core; the flux core is composed of the following raw materials in percentage by mass: 2-5wt% of diamond micropowder, 0.5-3wt% of tungsten powder, 37-40wt% of chromium powder, 8-12wt% of nickel powder, 1-6wt% of molybdenum powder, 2.5-4wt% of ferrosilicon powder, 1-2wt% of ferroboron powder, 0.5-3wt% of titanium carbide powder, 1-3wt% of ferroniobium powder, and the balance is reduced iron powder. The present invention simultaneously adds a variety of materials to the welding wire flux core for mixed enhancement, which can effectively improve the hardness and wear resistance of the coating, extend the service life of mechanical parts, and better meet the use requirements of mechanical parts with high surface wear resistance precision requirements.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of welding materials, and in particular relates to a wear-resistant enhanced flux-cored welding wire and a preparation method and application thereof. Background Art

[0002] Wear is one of the main reasons for the failure and performance degradation of mechanical parts. According to incomplete statistics, my country consumes about 3 million tons of metal wear-resistant materials every year, and the losses caused by material wear and failure amount to hundreds of billions of yuan. Wear-resistant coatings, as an effective means to improve the friction and wear properties of material surfaces, have been widely used in the field of industrial production.

[0003] Flux-cored welding wire is often used as the surface wear-resistant material of mechanical parts due to its unique advantages of high efficiency, low cost and automation. As the manufacturing industry develops towards high-end, precision, automation and green, the traditional iron-based flux-cored welding wire, although it has good weldability, has low coating hardness and its wear resistance is difficult to meet the requirements.

[0004] Diamond has ultra-high hardness, excellent wear resistance and compressive strength. Using diamond particles as the hard phase of the wear-resistant coating can effectively increase the hardness and wear resistance of the coating. However, when using a flux-cored wire containing diamond as a cladding material, a matching laser cladding technology is usually used to metallurgically bond it with the substrate surface to prepare a wear-resistant coating. Due to the high energy density and extremely high heat of the laser, diamond is easily carbonized during the cladding process. Excessive carbon will enter the weld and cause the coating to crack. In addition, the proportion of diamond in the coating will also decrease after carbonization, making it difficult to further improve the hardness and wear resistance of the coating, limiting its application. Summary of the invention

[0005] In order to solve the above problems, the purpose of the present invention is to provide a wear-resistant enhanced flux-cored welding wire, which can significantly improve the hardness and wear resistance of the obtained cladding coating after being used in the preparation of the substrate surface coating.

[0006] The present invention also provides a method for preparing the wear-resistant enhanced flux-cored welding wire, which is simple to operate and suitable for industrial application.

[0007] The present invention also provides application of the wear-resistant enhanced flux-cored welding wire.

[0008] In order to achieve the above objectives, the wear-resistant enhanced flux-cored welding wire of the present invention adopts the following technical solutions:

[0009] A wear-resistant enhanced flux-cored welding wire comprises an outer skin and a flux core; the flux core is composed of the following raw materials in percentage by mass: 2-5wt% of diamond micropowder, 0.5-3wt% of tungsten powder, 37-40wt% of chromium powder, 8-12wt% of nickel powder, 1-6wt% of molybdenum powder, 2.5-4wt% of ferrosilicon powder, 1-2wt% of ferroboron powder, 0.5-3wt% of titanium carbide powder, 1-3wt% of ferroniobium powder, and the balance is reduced iron powder.

[0010] In order to further improve the wear resistance and hardness of the cladding coating obtained by the flux-cored welding wire, the following typical flux core raw material composition can be used. The flux core is composed of the following raw materials in mass percentage: 5wt% diamond powder, 2wt% tungsten powder, 37wt% chromium powder, 10wt% nickel powder, 4wt% molybdenum powder, 2.5wt% ferrosilicon powder, 1.5wt% ferroboron powder, 2wt% titanium carbide powder, 2wt% ferroniobium powder, and the balance is reduced iron powder.

[0011] Based on the consideration of ensuring the particle size grading relationship of each raw material, cladding efficiency and coating strengthening effect, preferably, the particle size of the diamond micropowder is 20-50 μm; the particle size of the tungsten powder is 25-75 μm; the particle size of the chromium powder, nickel powder, molybdenum powder, ferrosilicon alloy powder, ferroboron alloy powder, titanium carbide powder, ferroniobium alloy powder and reduced iron powder is 50-70 μm.

[0012] The present invention does not specifically limit the outer skin material, and those skilled in the art can select a suitable outer skin material as needed to achieve the wrapping of the core. Preferably, the outer skin is a low-carbon cold-rolled steel strip. Furthermore, in the low-carbon cold-rolled steel strip, the C content is <0.05wt%, the Si content is <0.03%, the Mn content is 0.15-0.25%, the S and P contents are <0.03%, and the remainder is iron and unavoidable impurities.

[0013] The flux core welding wire is formed by wrapping the flux core powder with an outer skin. To improve the flux core wrapping and strengthening effect, preferably, the filling rate of the flux core is 40-50wt%.

[0014] Furthermore, the diameter of the wear-resistant enhanced flux-cored welding wire is 1.2 to 2.0 mm.

[0015] The method for preparing the wear-resistant enhanced flux-cored welding wire of the present invention adopts the following technical scheme:

[0016] The preparation method of the wear-resistant enhanced flux-cored welding wire comprises the following steps: mixing the flux-cored raw materials according to a proportion, then wrapping the flux-cored wire with an outer skin, and then drawing the wire to obtain the flux-cored wire.

[0017] The present invention also provides the application of the wear-resistant enhanced flux-cored welding wire as described above, specifically, the application in preparing a substrate coating by laser cladding.

[0018] By adding a flux-cored welding wire as a cladding material on the surface of the substrate, a laser is used to melt the cladding material and the thin layer on the surface of the substrate, thereby forming a metallurgically bonded cladding coating on the surface of the base layer. Based on the consideration of improving the wear resistance enhancement effect of the metallurgically bonded coating, preferably, the substrate is a steel substrate. More preferably, the substrate is a Q235 steel substrate.

[0019] Furthermore, the laser cladding process adopts argon protection; the purity of argon is 99.999%; the power of the laser cladding is 1.5-2.5kW, the wire feeding speed is 35-55mm / s, the welding speed is 3-5mm / s, the defocusing amount is 1-5mm, and the argon flow rate is 5-8L / min.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] (1) The wear-resistant enhanced flux-cored welding wire of the present invention optimizes the composition and ratio of the flux core and adds a variety of materials for mixed reinforcement, which can promote the refinement and homogenization of the weld metal structure and synergistically improve the hardness and wear resistance of the cladding coating.

[0022] The present invention simultaneously adds a specific amount of diamond powder and tungsten powder, a part of the diamond powder is dispersed in the cladding layer, hindering the movement of element dislocations and enhancing the wear resistance; the other part of the diamond is carburized during the laser cladding process, and the carburized diamond reacts with the tungsten powder added in the core to generate a WC hard phase in situ, further improving the wear resistance of the cladding coating.

[0023] In addition, the molybdenum and ferroboron alloys in the present invention can form Mo2FeB2 hard points and form a composite hard phase with titanium carbide to further improve the wear resistance of the coating. Various alloy elements such as Ni, W, Cr, and Nb form stable hard phases during the laser cladding process, which improves the bonding strength between the cladding coating and the substrate. Ferrosilicon alloy powder, as an important reducing agent, plays a role in deoxidation and improves the bonding strength of the coating. The test results show that compared with the traditional flux-cored welding wire, the wear-resistant enhanced flux-cored welding wire of the present invention has a strong bonding force between the cladding layer and the substrate, and the wear resistance can be significantly improved.

[0024] (2) The method for preparing the wear-resistant enhanced flux-cored welding wire of the present invention adopts an outer skin to wrap a flux core of a specific composition, which can prepare a flux-cored welding wire material with effectively improved wear resistance, and the preparation process is simple and suitable for industrial production.

[0025] (3) The present invention uses the wear-resistant enhanced flux-cored welding wire for laser cladding to prepare the substrate coating, wherein after tungsten powder is added to the flux core, it can not only effectively consume the carbon produced by diamond, but also generate wear-resistant enhanced WC compounds in situ, further improving the hardness and wear resistance of the coating, and extending the service life of the mechanical parts. Therefore, the surface cladding coating obtained by using the flux-cored welding wire provided by the present invention has significantly improved hardness and wear resistance, and can better meet the use requirements of mechanical parts with high surface wear resistance precision requirements. DETAILED DESCRIPTION

[0026] The technical solution of the present invention is further described below in conjunction with specific embodiments. However, it should be understood by those skilled in the art that the following embodiments are only used to illustrate the present invention and should not be regarded as limiting the scope of the present invention.

[0027] In the following examples, the raw materials involved are all conventional commercial products unless otherwise specified. Among them, the mass content of silicon in ferrosilicon alloy powder is ≥75%; the mass content of boron in ferroboron alloy powder is ≥18%; and the mass content of niobium in ferroniobium alloy powder is ≥98%.

[0028] In the following embodiments, the low carbon cold rolled steel strip used has a C content of <0.05wt%, a Si content of <0.03%, a Mn content of 0.15-0.25%, an S and P content of <0.03%, and the remainder is iron and unavoidable impurities.

[0029] Example 1

[0030] The wear-resistant enhanced flux-cored welding wire of this embodiment includes an outer skin and a flux core; the flux core is composed of the following raw materials in percentage by mass: 2wt% diamond powder, 0.5wt% tungsten powder, 40wt% chromium powder, 10wt% nickel powder, 3wt% molybdenum powder, 4wt% ferrosilicon powder, 2wt% ferroboron powder, 2wt% titanium carbide powder, 3wt% ferroniobium powder, and the balance is reduced iron powder.

[0031] Among them, the particle size of diamond micropowder is 25μm; the particle size of tungsten powder is 25μm; the particle size of chromium powder, nickel powder, molybdenum powder, ferrosilicon alloy powder, ferroboron alloy powder, titanium carbide powder, ferroniobium alloy powder and reduced iron powder is 50-70μm.

[0032] The method for preparing the wear-resistant enhanced flux-cored welding wire of this embodiment comprises the following steps:

[0033] The flux core raw materials are dried at 200°C according to the above ratio, and then mixed and rolled into an outer skin steel strip (low-carbon cold-rolled steel strip) with a width of 14 mm and a thickness of 0.25 mm. The flux core filling rate is 45wt%. After graded drawing, a wear-resistant reinforced flux cored welding wire with a diameter of 2.0 mm is obtained.

[0034] The application of the wear-resistant enhanced flux-cored welding wire of this embodiment is the application in the preparation of substrate coating by laser cladding. The specific preparation process of the substrate coating is: using Q235 steel as the substrate, the surface of the substrate is treated by sandblasting to remove impurities on the surface of the substrate; then the flux-cored welding wire of Example 1 is clad on the surface of the Q235 steel substrate by laser cladding technology. The laser cladding process adopts argon protection; the purity of argon is 99.999%. Cladding process parameters: power is 2.5kW, wire feeding speed is 50mm / s, welding speed is 3mm / s, argon flow rate is 7L / min, and defocusing amount is 5mm.

[0035] Example 2

[0036] The wear-resistant enhanced flux-cored welding wire of this embodiment includes an outer skin and a flux core; the flux core is composed of the following raw materials in percentage by mass: 2.5wt% diamond powder, 1.5wt% tungsten powder, 38wt% chromium powder, 10wt% nickel powder, 6wt% molybdenum powder, 4wt% ferrosilicon powder, 2wt% ferroboron powder, 2wt% titanium carbide powder, 3wt% ferroniobium powder, and the remainder is reduced iron powder.

[0037] Among them, the particle size of diamond micropowder is 50μm; the particle size of tungsten powder is 50μm; the particle size of chromium powder, nickel powder, molybdenum powder, ferrosilicon alloy powder, ferroboron alloy powder, titanium carbide powder, ferroniobium alloy powder and reduced iron powder is 50-70μm.

[0038] The method for preparing the wear-resistant enhanced flux-cored welding wire of this embodiment comprises the following steps:

[0039] The flux core raw materials are dried at 200°C according to the above ratio, and then mixed and rolled into an outer skin steel strip (low-carbon cold-rolled steel strip) with a width of 14 mm and a thickness of 0.25 mm. The flux core filling rate is 43wt%. After graded drawing, a wear-resistant enhanced flux cored welding wire with a diameter of 1.6 mm is obtained.

[0040] The application of the wear-resistant enhanced flux-cored welding wire of this embodiment is the application in the preparation of substrate coating by laser cladding. The specific preparation process of the substrate coating is: using Q235 steel as the substrate, the surface of the substrate is treated by sandblasting to remove impurities on the surface of the substrate; then the flux-cored welding wire of Example 2 is clad on the surface of the Q235 steel substrate by laser cladding technology. The laser cladding process adopts argon protection; the purity of argon is 99.999%. Cladding process parameters: power is 2kW, wire feeding speed is 55mm / s, welding speed is 3.5mm / s, argon flow rate is 7L / min, and defocus is 3.5mm.

[0041] Example 3

[0042] The wear-resistant enhanced flux-cored welding wire of this embodiment includes an outer skin and a flux core; the flux core is composed of the following raw materials in percentage by mass: 4wt% diamond powder, 3wt% tungsten powder, 37wt% chromium powder, 10wt% nickel powder, 4.5wt% molybdenum powder, 3.5wt% ferrosilicon powder, 2wt% ferroboron powder, 2wt% titanium carbide powder, 1.5wt% ferroniobium powder, and the remainder is reduced iron powder.

[0043] Among them, the particle size of diamond micropowder is 50μm; the particle size of tungsten powder is 75μm; the particle size of chromium powder, nickel powder, molybdenum powder, ferrosilicon alloy powder, ferroboron alloy powder, titanium carbide powder, ferroniobium alloy powder and reduced iron powder is 50-70μm.

[0044] The method for preparing the wear-resistant enhanced flux-cored welding wire of this embodiment comprises the following steps:

[0045] The flux core raw materials are dried at 200°C according to the above ratio, and then mixed and rolled into an outer skin steel strip (low-carbon cold-rolled steel strip) with a width of 14 mm and a thickness of 0.25 mm. The flux core filling rate is 42wt%. After graded drawing, a wear-resistant enhanced flux cored welding wire with a diameter of 1.2 mm is obtained.

[0046] The application of the wear-resistant enhanced flux-cored welding wire of this embodiment is the application in the preparation of substrate coating by laser cladding. The specific preparation process of the substrate coating is: using Q235 steel as the substrate, the surface of the substrate is treated by sandblasting to remove impurities on the surface of the substrate; then the flux-cored welding wire of Example 3 is clad on the surface of the Q235 steel substrate by laser cladding technology. The laser cladding process adopts argon protection; the purity of argon is 99.999%. Cladding process parameters: power is 2kW, wire feeding speed is 50mm / s, welding speed is 5mm / s, argon flow rate is 8L / min, and defocus is 2.5mm.

[0047] Example 4

[0048] The wear-resistant enhanced flux-cored welding wire of this embodiment includes an outer skin and a flux core; the flux core is composed of the following raw materials in percentage by mass: 5wt% diamond powder, 2wt% tungsten powder, 37wt% chromium powder, 10wt% nickel powder, 4wt% molybdenum powder, 2.5wt% ferrosilicon powder, 1.5wt% ferroboron powder, 2wt% titanium carbide powder, 2wt% ferroniobium powder, and the remainder is reduced iron powder.

[0049] Among them, the particle size of diamond micropowder is 30μm; the particle size of tungsten powder is 25μm; the particle size of chromium powder, nickel powder, molybdenum powder, ferrosilicon alloy powder, ferroboron alloy powder, titanium carbide powder, ferroniobium alloy powder and reduced iron powder is 50-70μm.

[0050] The method for preparing the wear-resistant enhanced flux-cored welding wire of this embodiment comprises the following steps:

[0051] The flux core raw materials are dried at 200°C according to the above ratio, and then mixed and rolled into an outer skin steel strip (low-carbon cold-rolled steel strip) with a width of 14 mm and a thickness of 0.25 mm. The flux core filling rate is 44wt%. After graded drawing, a wear-resistant enhanced flux cored welding wire with a diameter of 1.4 mm is obtained.

[0052] The application of the wear-resistant enhanced flux-cored welding wire of this embodiment is the application in the preparation of substrate coating by laser cladding. The specific preparation process of the substrate coating is: using Q235 steel as the substrate, the surface of the substrate is treated by sandblasting to remove impurities on the surface of the substrate; then the flux-cored welding wire of Example 4 is clad on the surface of the Q235 steel substrate by laser cladding technology. The laser cladding process adopts argon protection; the purity of argon is 99.999%. Cladding process parameters: power is 1.5kW, wire feeding speed is 35mm / s, welding speed is 3mm / s, argon flow rate is 5L / min, and defocus is 1mm.

[0053] Comparative Example 1

[0054] The flux-cored welding wire of this comparative example is the common wear-resistant flux-cored welding wire D707 on the market.

[0055] The wear-resistant flux-cored wire D707 was used for laser cladding to prepare the substrate coating. The specific preparation process of the substrate coating is referred to Example 4, the difference between the two is that the flux-cored wire used is different, and the other parameters are the same.

[0056] Comparative Example 2

[0057] The preparation process of the flux-cored welding wire in this comparative example is basically the same as that of Example 4, except that the flux core used in this comparative example does not contain diamond powder.

[0058] The application of the flux-cored welding wire in this comparative example in preparing a substrate coating by laser cladding is basically the same as that in Example 4, except that different flux-cored welding wires are used, and the other parameters are the same.

[0059] Comparative Example 3

[0060] The preparation process of the flux-cored welding wire in this comparative example is basically the same as that in Example 4, except that the flux core used in this comparative example does not contain tungsten powder.

[0061] The application of the flux-cored welding wire in this comparative example in preparing a substrate coating by laser cladding is basically the same as that in Example 4, except that different flux-cored welding wires are used, and the other parameters are the same.

[0062] Comparative Example 4

[0063] The preparation process of the flux-cored welding wire in this comparative example is basically the same as that in Example 4, except that: this comparative example uses 1.2% diamond micropowder, 2wt% tungsten powder, 37wt% chromium powder, 10wt% nickel powder, 4wt% molybdenum powder, 2.5wt% ferrosilicon alloy powder, 1.5wt% ferroboron alloy powder, 2wt% titanium carbide powder, 2wt% ferroniobium alloy powder, and the balance is reduced iron powder.

[0064] The application of the flux-cored welding wire in this comparative example in preparing the substrate coating by laser cladding is basically the same as that in Example 4, the difference between the two is that different flux-cored welding wires are used, and the other parameters are the same.

[0065] Test case performance test

[0066] With reference to the national standard GB / T 4340.1-2009 hardness test and GB / T 12444-2006 wear test method, the wear performance test of the cladding coatings obtained after laser cladding of the flux-cored welding wires of Examples 1 to 4 and Comparative Examples 1 to 4 was carried out. The results are shown in Table 1.

[0067] Table 1 Performance test results of the cladding layer obtained by flux-cored welding wire

[0068] Experimental Group Hardness / HV Wear rate g / h Example 1 885 5.5 Example 2 912 4.6 Example 3 1033 4.1 Example 4 1050 2.3 Comparative Example 1 790 7.1 Comparative Example 2 704 10.4 Comparative Example 3 781 7.3 Comparative Example 4 810 6.9

[0069] It can be seen from Table 1 that the wear-resistant enhanced flux-cored welding wire of the present invention has better hardness and wear resistance than the flux-cored welding wires of Comparative Examples 1 to 4, which shows that the present invention uses a variety of materials for mixed reinforcement, especially after adding a specific amount of diamond powder and tungsten powder, it can not only consume the carbon produced by diamond, but also generate wear-resistant enhanced WC compounds in situ, effectively improve the hardness and wear resistance of the coating, and extend the service life of mechanical parts.

[0070] In summary, the flux-cored welding wire provided by the present invention can significantly improve the hardness and wear resistance of the substrate and extend the service life of the substrate on the basis of giving full play to the advantages of diamond. Therefore, the present invention can effectively broaden the application scope of the flux-cored welding wire and better meet the use requirements of mechanical parts with high surface wear resistance precision requirements.

Claims

1. A wear-resistant enhanced flux-cored welding wire, characterized in that: The invention comprises an outer skin and a core; the core is composed of the following raw materials in percentage by mass: 2-5wt% of diamond micropowder, 0.5-3wt% of tungsten powder, 37-40wt% of chromium powder, 8-12wt% of nickel powder, 1-6wt% of molybdenum powder, 2.5-4wt% of ferrosilicon powder, 1-2wt% of ferroboron powder, 0.5-3wt% of titanium carbide powder, 1-3wt% of ferroniobium powder, and the remainder is reduced iron powder.

2. The wear-resistant enhanced flux-cored welding wire according to claim 1, characterized in that: The flux core is composed of the following raw materials in percentage by mass: 5wt% diamond powder, 2wt% tungsten powder, 37wt% chromium powder, 10wt% nickel powder, 4wt% molybdenum powder, 2.5wt% ferrosilicon powder, 1.5wt% ferroboron powder, 2wt% titanium carbide powder, 2wt% ferroniobium powder, and the remainder is reduced iron powder.

3. The wear-resistant enhanced flux-cored welding wire according to claim 1, characterized in that: The particle size of the diamond micropowder is 20-50 μm; the particle size of the tungsten powder is 25-75 μm; the particle size of the chromium powder, nickel powder, molybdenum powder, ferrosilicon alloy powder, ferroboron alloy powder, titanium carbide powder, ferroniobium alloy powder and reduced iron powder is 50-70 μm.

4. The wear-resistant enhanced flux-cored welding wire according to any one of claims 1 to 3, characterized in that: The outer skin is a low-carbon cold-rolled steel strip.

5. The wear-resistant enhanced flux-cored welding wire according to any one of claims 1 to 3, characterized in that: The filling rate of the drug core is 40-50wt%.

6. The wear-resistant enhanced flux-cored welding wire according to any one of claims 1 to 3, characterized in that: The diameter of the wear-resistant enhanced flux-cored welding wire is 1.2-2.0 mm.

7. The method for preparing the wear-resistant enhanced flux-cored welding wire according to claim 1, characterized in that: The method comprises the following steps: mixing the core raw materials according to the proportion, wrapping the core with the outer skin, and then drawing the core to obtain the product.

8. The use of the wear-resistant enhanced flux-cored welding wire according to any one of claims 1 to 6, characterized in that: Application in laser cladding preparation of substrate coating.

9. The use of the wear-resistant enhanced flux-cored welding wire according to claim 8, characterized in that: The substrate is a steel substrate.

10. The use of the wear-resistant enhanced flux-cored welding wire according to claim 8 or 9, characterized in that: The laser cladding process adopts argon protection; the power of the laser cladding is 1.5-2.5kW, the wire feeding speed is 35-55mm / s, the welding speed is 3-5mm / s, the defocusing amount is 1-5mm, and the argon flow rate is 5-8L / min.